Application of amide proton transfer imaging for the diagnosis of neonatal hypoxic–ischemic encephalopathy - Chen, Sijin; Liu, Xilong; Lin, Jie; Mei, Yingjie; Deng, Kan; Xue, Qiao; Song, Xiaoyan; Xu, Yikai (Frontiers in Pediatrics, 2022)
Objective This study aimed to evaluate cerebral amide proton transfer signal intensity (SI) among controls, hypoxic–ischemic encephalopathy (HIE) neonates with normal conventional magnetic resonance imaging (HIE/MRI−) findings, and HIE neonates with abnormal conventional MRI (HIE/MRI+) findings. Methods Forty neonates diagnosed with neonatal HIE and sixteen normal neonates were evaluated. All neonates underwent conventional MRI scans and APT imaging. Cerebral APT SIs were compared to identify cerebral regions with significant APT changes among sixteen controls, thirteen HIE/MRI− patients, and twenty–seven HIE/MRI+ patients. Results Significantly increased APT SIs were observed in the HIE/MRI− group compared with controls, in the left insula, right occipital lobe, left cingulate gyrus (posterior part), and corpus callosum. Significantly increased APT SIs were found in the HIE/MRI+ group compared with controls, in the right anterior temporal lobe (medial part), anterior parts of the right parahippocampal and ambient gyri, left superior temporal gyrus (middle part), left insula, left cingulate gyrus (posterior part), and right lentiform nucleus. No significant APT SI differences were observed in the cerebellum and brainstem among the three groups. Conclusion Amide proton transfer imaging plays an important role in detecting hypoxic–ischemic encephalopathy regardless of conventional MRI findings. Changes in APT signal intensity may provide important insights into the characterization of the cerebral internal environment. This study suggests that APT imaging could be used as a complement to conventional MRI in the detection of hypoxic–ischemic encephalopathy in clinical practice.